Effect of pH Variation on Solubility of Seed Protein of Pisum sativum - Naga Bhushana Rao, G.; Shrivastava, S.K. (Asian Journal of Chemistry, 2010)
Increased utilization of legume protein by the food industry has increased research in the utilization of legume or seed proteins in foods. Solubility is a critical functional property, since a protein generally has to be in solution in order to exert its other desirable functional characteristics. Nitrogen solubility index and protein dispersibility index (PDI) are the two most common methods of evaluating solubility characteristics. Hence in this study new variety breeder seeds (Arkel, Pusa pragati, IPF-99-25, JP-885, MM-15 and JM-6) of Pisum sativum are studied for protein solubility at wide range of pH from 0.5 to13.5. The knowledge of protein structure and size of different legumes seeds, of different varieties, will bring an understanding of the protein properties. This will permit manipulation of these properties for food product development.